2018
DOI: 10.1007/s00401-018-1844-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of histone H3K27me3 identifies a subset of meningiomas with increased risk of recurrence

Abstract: Epigenetic patterns on the level of DNA methylation have already been shown to separate clinically relevant subgroups of meningiomas. We here set out to identify potential prognostic implications of epigenetic modification on the level of histones with focus on H3K27 trimethylation (H3K27me3). H3K27me3 was assessed by immunohistochemistry on 232 meningiomas from 232 patients. In 194 cases, trimethylation was detected in tumor cells. In 25 cases, staining was limited to vessels while all tumor cells were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 42 publications
4
97
0
Order By: Relevance
“…Sahm et al devised a DNA methylation-based grading system for meningioma that accurately stratified risk of recurrence in meningiomas more accurately than current WHO grading by analyzing methylation patterns in 40 genes known to contribute to meningioma genesis and progression ( 23 ). Similarly, Katz et al also demonstrate that methylation patterns on the H3 histone could predict recurrence of WHO grade I and II meningiomas ( 25 ). One recent study highlighted the use of RNA sequencing and whole-exome sequencing to predict recurrence more accurately than current WHO criteria ( 24 ).…”
Section: Prognostic Factors For Meningiomasmentioning
confidence: 90%
See 1 more Smart Citation
“…Sahm et al devised a DNA methylation-based grading system for meningioma that accurately stratified risk of recurrence in meningiomas more accurately than current WHO grading by analyzing methylation patterns in 40 genes known to contribute to meningioma genesis and progression ( 23 ). Similarly, Katz et al also demonstrate that methylation patterns on the H3 histone could predict recurrence of WHO grade I and II meningiomas ( 25 ). One recent study highlighted the use of RNA sequencing and whole-exome sequencing to predict recurrence more accurately than current WHO criteria ( 24 ).…”
Section: Prognostic Factors For Meningiomasmentioning
confidence: 90%
“…One recent study highlighted the use of RNA sequencing and whole-exome sequencing to predict recurrence more accurately than current WHO criteria ( 24 ). Interestingly, in all these studies, the authors report that their methods accurately predicted recurrence in a significant subset of WHO Grade I tumors where recurrence is typically low ( 23 25 ). Studies with larger sample sizes are needed to assess how tumor microenvironment and immune infiltrate impact meningioma recurrence and progression.…”
Section: Prognostic Factors For Meningiomasmentioning
confidence: 99%
“…H3K27me3 and DNA hypomethylation decreases without recurrent genetic alterations in HCC displays that epigenetic mechanisms are the core of HCC occurrence [29][30][31][32][33][34][35]. Further, some studies indicated that decreased H3K27me3 is not deregulated by genes but epigenetics [36,37].…”
Section: Disscusionmentioning
confidence: 99%
“…Katz et al. reported that complete loss of nuclear staining for H3K27 trimethylation (H3K27me3) was closely associated with more aggressive DNA‐methylation subgroups, and hence a potential biomarker in the routine diagnostic work‐up of meningiomas.…”
Section: Meningiomasmentioning
confidence: 99%
“…A study by Olar et al (161) also found that DNA methylation analysis of meningiomas reliably identified patients with risk of tumor recurrence. Katz et al (167) reported that complete loss of nuclear staining for H3K27 trimethylation (H3K27me3) was closely associated with more aggressive DNA-methylation subgroups, and hence a potential biomarker in the routine diagnostic work-up of meningiomas.…”
Section: Meningiomasmentioning
confidence: 99%